Digital divide, e-government and trust in public service: The key role of education - Mesa, Diego (Frontiers in Sociology, 2023)
The Italian public administration (PA) has always had problems with slowness and inefficiency. In 2021, the Italian government made a massive investment in digitizing PA as part of an extraordinary recovery plan, with more than 200 billion euro to revitalize the country. This paper aims to investigate how educational inequalities affect the relationship between Italian citizens and PA in this phase of the digital transition. The study is based on a web survey conducted in March and April 2022 among a national sample of 3,000 citizens aged 18–64. The data shows that more than three-quarters of respondents have already used a public service at least once via an online channel. Few are aware of the reform plan, however, and more than one-third fear that the digitization of public services will make things worse for citizens. Through a regression analysis, the study confirms the centrality of the influence of education on the use of digital public services compared to the other spatial and social variables considered. Trust in PA is also correlated with education and employment status and is higher among those who have used digital public services. The survey thus highlights that the educational and cultural dimension is a crucial aspect as a lever to counter the digital divide and promote digital citizenship rights. It reveals the need to activate facilitation and accompaniment processes for citizens with less digital skills and experience who risk being excluded or penalized by the new arrangement and having their distrust toward the PA and state exacerbated.